STUDIES ON CROP PERFORMANCE OF TROPICAL TASAR SILKWORM ANTHERAEA MYLITTA (DRURY) IN ZIZIPHUS MAURITIANA LAM. (BER), AN AVAILABLE SECONDARY FOOD PLANT IN SIMILIPAL BIOSPHERE RESERVE, ODISHA FOR COMMERCIAL EXPLOITATION - BASKEY, SAROJINEE; SATAPATHY, SUBRAT; BASTIA, AKHAYA KUMAR (The Bioscan, 2014)
The availability of food plants and their nutritional status play a pivotal role for successful tasar culture both in commercial and seed crops. In the present investigation an experimental rearing of Indian tasar silkworm Antheraea mylitta Drury was carried out during commercial season in the Kalapathar village of Tasar Rears CoOperative Society (TRCS), Bhuasuni in the district Mayurbhanj of Odisha state located in the peripheral zone of Similipal Biosphere Reserve. The experiment was undertaken to study the effect of Ziziphus mauritiana Lam. (Ber), a secondary food plant on cocoon crop performance. The rearing performance of the silkworm on Z. mauritiana in terms of cocoon per DFLS and silk ratio was found comparable to that with Terminalia tomentosa (Asan), a primary food plant species of A. mylitta Drury. It is seen that the crop production (yield) is about 18 to 21% in terms of ERR and is comparable to that of traditional primary food plant i.e. 24-28%. This study indicates the commercial perspective and feasibility of Ziziphus mauritiana as alternate food plant of tasar silkworm rearing in the period of exigency.